IMPLEMENTASI NILAI-NILAI KECERDASAN SPIRITUAL DI YAYASAN PONDOK MODERN AL-RIFA’IE SATU MALANG - Latifatur Rohmah; Muhammad Hanif; Ika Anggraheni (VICRATINA, 2019)
Spiritual intelligence (SQ) is intelligence that can help humans heal themselves as a whole. There are so many people who are currently living a life full of wounds and disarray, they long for harmony in their lives. Human existence in life is to carry out the task of the Caliphate which is to make the world a place that is in accordance with the will of Allah SWT, this goal can only be fulfilled if humans are aware of their duties. While in today's instantaneous era, humans experience a crisis that is very alarming, because along with the advancement of science and technology with all its variety it has not succeeded in elevating the dignity of human life. disappearing. Modern Al-Rifa'ie One Gondanglegi Malang Residence became the object of research in this thesis which is one of the educational institutions that use the Islamic boarding school system. Keywords: Value, Spiritual Intelligence